The diversity of flora at the Late Pliocene era in the Cisubuh Formation based on palynological data - Rachmad Setijadi; Sri Widodo Agung Soedy; Rully Rahardian (Jurnal Ilmu Lingkungan)
Palynological evidence on past time gives features on plant diversity. The objective of this research was to determine the flora diversity in the past based on the palynological evidence in the form of pollen and spores (palynomorphs) that stored in sediments in the Cisubuh Formation. This research consisted of two stages, field sampling, and laboratory observation. A total of 16 samples on Cisubuh Formation on Rengasdengklok area, West Java Indonesia have been identified for their fossil content. Sixty-seven palynomorphs have been identified, comprised of 53 pollen taxa and 14 type of spores. Of the 67 palynomorph taxa, 40 were arboreal pollen, 12 were non-arboreal pollen, and 15 were Pteridophytes. The geological age of Cisubuh Formation was Late Pliocene, as indicated by Dacrycarpidites australiensis and without the presence of Stenochlaenidites papuanus. Based on the palynological evidence, the flora diversity in each layer sediment of the Cisubuh Formation showed high similarity (87%).